AlphaVBeta3 Integrin expression within uterine endometrium in unexplained infertility: a prospective cohort study - Ahmed Elnaggar; Amr H. Farag; Mohamed E. Gaber; Mohamed Abdel Hafeez; Mohamed S. Ali; Alaa M. Atef (BMC, 2017)
Abstract Background Implantation defect is one of these contributing factors for unexplained infertility. In the mid-luteal phase, when implantation is expected to happen, Integrins expression is remarkably increased. So, Integrins could potentially serve as markers for the frame of the window of implantation. αVβ3 integrin could have a role as a potential receptor for embryonic attachment. The aim of the current study is to investigate whether the women with unexplained infertility have a pattern of expression of endometrial αvβ3 integrin that could differ from those who have normal fertility or not. Method Two groups of women have been included in this study. The first group was the Unexplained Infertility Group. This group included women diagnosed with unexplained primary infertility. The second group was the fertile Group, which included fertile parous women presented to the family planning clinic seeking contraception. 2D transvaginal ultrasound scan (TVS) was performed six days after detecting urinary LH surge. (TVS) was used to measure endometrial thickness, and subendometrial blood flow color Doppler Resistance Index (RI). On the same day of transvaginal ultrasound, endometrial samples were taken using the Endocell® office suction sampler for Immunohistochemistry (IHC) study using monoclonal mouse IgG antibodies to detect endometrial αvβ3 integrin. Results Thirty-five fertile women with a diagnosis of unexplained infertility were included as a group I [Unexplained infertility Group] along with an equal number of fertile women as group II [Fertile Group]. The group of women with a diagnosis of unexplained infertility had a significantly lower αvβ3 integrin score when compared to the fertile group (median score 0, range:0-2 and median score 1, range: 1-3 and for infertile and fertile groups respectively, P < 0.0001). In addition, the unexplained infertility group had significantly higher subendometrial flow RI and Significantly thinner endometrial thickness. Conclusion This study showed that Alpha v Beta 3 integrin is a significantly lower in endometrium in cases of unexplained infertility, which may suggest that underexpression of Alpha v Beta 3 integrin in human endometrium could be linked to defective uterine receptivity, and play a role as an unrecognized cause of infertility in this population of women. We need larger studies of adequate statistical power, ideally investigating more than one menstrual cycle in the same woman, to investigate the usefulness of using these molecular molecules in clinical practice.